EXPERIMENTAL GETARAN PADA MODEL TRANSMISI RODA GIGI DALAM JENIS LURUS - Eddy, Noor; Nuryanto, Nuryanto (Program Studi Teknik Mesin, Universitas Trisakti, 2006)
In a row of rise competition in the industry world motivate each industry to grow up the machinesefficiency that they have with apply the correct maintenance method, as predictive maintenance method. Thismethod are utilize a parameter signal vibrate that appearfor monitoring the machine condition. With inspectthe vibrate level with periodic, then something abnormal can he detection before a bigger or fatal damagehappen. The vibrate characteristic that revived by one of damage is have a unique characteristic, thisresearch is headfor know and study the characteristic. In this research used a internal gear transmissionsystem with a spur kindas a model, vibrate characteristic analysis is do with use a Dynamic Signal Analyzer(DSA). than it can be inspect thephenomenon which happen in the systemand the out influence (load) to thephenomenon that happen